Fifteen years of innovative leadership : Professor Sture Brändström and the development of the research environment at the Department of Music and Media in Piteå - Ferm, Cecilia; Karlsen, Sidsel (Luleå tekniska universitet, Musik och dans, 2010)
Godkänd; 2010; 20100825 (andbra)